Disney Classics between Feminism and Victimization of Women: A Historical Analysis - Abdulqadr, Kezhan Salar; Sharif, Ranjdar Hama; Omer, Roz Jamal; Saeed, Alan Ali; Abdul, Zanyar Kareem (Technium Social Sciences Journal, 2021)
This paper focuses on the two contradictory themes of feminism and victimizing women in Disney Classics, a series of films which are based on famous fairy tales and the development of the changes undergone by these stories over time. The study is carried out through an analysis of the themes of the stories with a critical feminist approach in three chronological stages. Previous studies have explored these themes, but no report to date has used a chronological approach to compare the significance of the mentioned themes with the stages of feminism. These stories develop in line with developments in society and widen their perspective when examined through a feminist lens, and this change is also reflected in the Disney treatments of these tales. Despite the similarities in the plots of Snow White and the Seven Dwarfs, Cinderella, The Sleeping Beauty, and The Little Mermaid, the representations of the voice and agency of the female characters in these films differs significantly, especially in the case of Snow White.